DMT1 iron uptake in the PNS: bridging the gap between injury and regeneration. Issue 10 (7th October 2015) - Martinez-Vivot, Rocío; Copello, Guillermo; Leal, Celeste; Piñero, Gonzalo; Usach, Vanina; Rozenszajn, Mijael; Morelli, Laura; Setton-Avruj, Clara Patricia
<x xml:space="preserve">Abstract</x> This work supports DMT1 involvement in iron regulation in SCs, its role as a sensor of iron necessity and its ability to guarantee iron supply during myelination and remyelination.